Impact Analysis of Day Trans Transportation Services on Population Mobility in the City of Bandung - Muh. Akbar Aziz; A Fadel Muhammad; Romansyah Sahabuddin (Universitas Muhammadiyah Palu, 2024)
Day Trans is a company that comes as one of the solutions that can help improve the situation in Bandung City. This study aims to analyze the impact of Day Trans transportation services on population mobility in Bandung City. The research method used is qualitative research by collecting data through in-depth interviews with respondents who use Day Trans services. The results showed that Day Trans transportation services made a significant contribution in improving the accessibility and availability of public transportation in Bandung City. Research respondents acknowledged that since Day Trans has been available, they can easily access various destinations in the city. Day Trans also reduces congestion and air pollution in Bandung City as some residents switch from private vehicles to public transportation. This study recommends several corrective actions. Among other things, there is a need to adjust bus schedules to the needs of residents to reduce long waiting times or add routes and travel frequencies to increase the affordability of Day Trans to various destinations, etc. This will help reduce congestion, pollution and air pollution in Bandung. This will help reduce congestion, pollution and improve the quality of life of residents while promoting environmental sustainability in the city.